Estudio de la percepción y conocimientos sobre temas ambientales, cambio climático y propuesta de educación ambiental en la parroquia Eloy Alfaro, cantón Latacunga 2023” - Deker Moran, Juleidy Jamilet (2024)
In the current degree work it was carried out an study regarding perception and relative knowledge related to environmental subjects and climate change, as well as the formulation of an environmental education proposal in Eloy Alfaro, Latacunga 2023. A qualitative, bibliographic and descriptive research design was applied to carry out this research work, Projects degree and reviews of scientific literature provided support for the methodology design which had to do with environmental education and climate change. To gather data used in the study, the Eloy Alfaro parish's residents were surveyed and classified into accessible neighborhoods in order to apply the direct observation technique. The formula for the 379 population to be surveyed was calculated using the finite sampling formula. The survey was based on two phases; the survey allowed for the identification of personal information in the first phase and the observation of the population's knowledge regarding environmental education and climate change in the second phase. The analysis's findings showed that, while a sizable portion of the sample 93.14 percent knew about the subject matter, they lacked sufficient direction for disseminating information on climate change mitigation strategies. Data collection allowed to observe shortcomings in public institutions' activities to combat climate change by demonstrating a lack of action. Lastly, an integral environmental education proposal was created to raise Parish members' awareness and encourage their active involvement in environmental preservation and prevention. In Eloy Alfaro Parish, this idea was intended to serve as a catalyst for group actions focused on sustainability and environmental care.